The Sudetic Geostrada – an idea of geological and landscape studies heritage with inventarization of the objects of abiotic nature - Słomka, Tadeusz; Bartuś, Tomasz; Mastej, Wojciech; Łodziński, Marek; Mayer, Wojciech; Strfaniuk, Michał; Doktor, Marek; Koźma, Jacek; Cwojdziński, Stefan; Stachowiak, Andrzej (Geotourism/Geoturystyka)
The aim of the paper is presentation of geological and landscape studies with the inventarization of abiotic nature objects located along proposed trail “The Leszek Sawicki Sudetic Geostrada”. Through detailed descriptions of the trail and proposals of development of selected, most attractive geosites of geological-mining heritage, the project should aim to spread geological knowledge of the Sudety Mts. among the non-professionals. Using the passable roads, the trail was led along the main ridges of the Sudety Mts. in both the Polish and the Czech parts, through less popular and rarely visited but also interesting parts of the Sudety Mts. and their foreland. Polish parts of the Geostrada (ca 285 km) were such determined to reach as much the most attractive geosites as possible in the 10-kilometers-wide zone (±5 km from both sides of the trail).